“Home and Native Land”: Aboriginal Young Women and Homelessness in the City - Ruttan, Lia; LaBoucane-Benson, Patti; Munro, Brenda (First Peoples Child & Family Review, 2010)
The homelessness of Aboriginal young women takes place in the historical context of lost homes and lost homelands. This article focuses on homeless Aboriginal women in the city of Edmonton and explores their perception of this experience. Involving nine young women who were interviewed over a two year period, researchers further investigated the historical profiles of their families and their attempts to transition out of homelessness. Part of a larger study of the homeless experience of eighteen girls and young women in Edmonton, this article breaks out data that focuses on the experience of Aboriginal participants and contextualizes their discourse in light of enforced home loss in western Canada. While their experience overlaps with the non-Aboriginal participants in our study we also find significant cultural and historically located differences.